2020
DOI: 10.7196/ajhpe.2020.v12i3.1373
|View full text |Cite
|
Sign up to set email alerts
|

The influence of context on the teaching and learning of undergraduate nursing students: A scoping review

Abstract: The role that context plays in the teaching and learning space has been well documented, characterised as complex and dynamic, and changing in response to competing international and local demands. [1] This complexity has been recognised in health professions education, with calls for the adaptation of existing curricula that do not adequately equip graduates in the health professions to meet the needs of the communities they serve. [2,3] Understanding the context-the surroundings, circumstances, environments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(133 reference statements)
0
1
0
1
Order By: Relevance
“…It can be seen from Figure 6 that 47.2% of the students think that teachers sometimes organize group competitions, 37.5% think that teachers organize group competitions every time, 12% think that they seldom organize group competitions, and 3.4% think that they have never participated in group competitions in the process of creating the context in the primary English class Advances in Multimedia 3 [6].According to the survey results, teachers do not often use the form of group cooperation in teaching, and a small number of students think that there has never been a group competition. rough classroom observation, it is found that in English class, the group activities adopted by teachers in context teaching, such as group competitions, are simply to complete the teaching tasks and get close to the teaching objectives, and do not really reflect the significance and value of group cooperative learning [7,8].…”
Section: Investigation On the Cooperative Form Of Middle Schoolmentioning
confidence: 99%
“…It can be seen from Figure 6 that 47.2% of the students think that teachers sometimes organize group competitions, 37.5% think that teachers organize group competitions every time, 12% think that they seldom organize group competitions, and 3.4% think that they have never participated in group competitions in the process of creating the context in the primary English class Advances in Multimedia 3 [6].According to the survey results, teachers do not often use the form of group cooperation in teaching, and a small number of students think that there has never been a group competition. rough classroom observation, it is found that in English class, the group activities adopted by teachers in context teaching, such as group competitions, are simply to complete the teaching tasks and get close to the teaching objectives, and do not really reflect the significance and value of group cooperative learning [7,8].…”
Section: Investigation On the Cooperative Form Of Middle Schoolmentioning
confidence: 99%
“…El contexto educativo y las circunstancias y ambientes dentro de los cuales ocurre el aprendizaje cobran especial importancia (18). Investigadores han explorado el contexto, argumentando que este se extiende más allá del entorno físico, su influencia comprende lo físico, semántico y afectivo (19). Las investigaciones realizadas demuestran que existe una fuerte asociación entre la percepción de los estudiantes sobre su entorno de aprendizaje y sus resultados académicos y está ligado a su comportamiento (20)(21)(22).…”
Section: Discussionunclassified